Analysis of Court Decisions in Divorce Lawsuits which were Rejected Due to Failure to Fulfill the Dispute Proof Requirements: Case Study of the Binjai District Court - Tambunan, Yusna Elfrida Br; Pinem, Octa Vioni; Gultom, Joshua Hery Cristian; Sembiring, Vanessa Uli; Siahaan, Parlauangan G (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The desired divorce or divorce status can be achieved if it is carried out in accordance with existing procedures. Such as, the conditions on how a relationship is allowed to divorce, the reasons put forward are valid or not, the procedures followed are appropriate or not, this is very important to pay attention to. The author will analyze the Court Decision in a divorce lawsuit which was rejected because the evidentiary requirements were not fulfilled. dispute: case study of the Binjai District Court. The method used in this research uses qualitative research methods, namely case studies with a normative legal research or doctrinal research approach, using secondary data. In divorce cases, the plaintiff must be able to prove that the plaintiff is involved in a dispute that fulfill the divorce requirements according to applicable law. In Indonesia, the requirements for divorce are regulated in Law Number 1 of 1974 concerning Marriage. One of the grounds for divorce is the existence of a dispute that cannot be reconciled or it could be said to be a prolonged conflict between husband and wife. The court rejected the divorce lawsuit because the requirements for proving the dispute were not fulfilled. This decision shows how important the principles of evidence and legal certainty are in divorce cases. Divorce cannot be granted if there is no strong evidence that the dispute cannot be resolved.